High-performance finite-element simulations of seismic wave propagation in three-dimensional nonlinear inelastic geological media - Dupros, Fabrice; De Martin, Florent; Foerster, Evelyne; Komatitsch, Dimitri; Roman, Jean (Parallel computing, 2010)
We present finite-element numerical simulations of seismic wave propagation in non linear inelastic geological media. We demonstrate the feasibility of large-scale modeling based on an implicit numerical scheme and a nonlinear constitutive model. We illustrate our methodology with an application to regional scale modeling in the French Riviera, which is prone to earthquakes. The PaStiX direct solver is used to handle large matrix numerical factorizations based on hybrid parallelism to reduce memory overhead. A specific methodology is introduced for the parallel assembly in the context of soil nonlinearity. We analyse the scaling of the parallel algorithms on large-scale configurations and we discuss the physical results.